Quantitative analysis of local bone graft harvested from the posterior elements during posterior spinal fusion in Adolescent Idiopathic Scoliosis patients - Choo, Qi Qi; Chiu, Chee Kidd; Lisitha, Kulathunga Arachchige; Chan, Chris Yin Wei; Kwan, Mun Keong (Elsevier, 2019)
Objective: This study analyses the quantity of local bone graft obtained from different anatomical parts of the posterior elements during corrective surgery for Adolescent Idiopathic Scoliosis patients. Summary of background data: Locally harvested autogenous bone graft eliminates possible donor site morbidity and has all the important basic bone graft properties such as osteoinductivity, osteogenicity and osteoconductivity. Its usage was reported to be adequate to achieve fusion but none had quantifies the amount of local bone graft harvested. Methods: Total of 40 AIS patients were recruited in the study. All posterior spinal fusion surgeries were performed by the same dual surgeons and same anesthetist with a single observer collecting and measuring bone grafts harvested. The bone grafts harvested from each respective posterior element (spinous processes, laminas, facets and transverses processes) and measured accordingly. Results: There were 36 females and 4 males. Amongst cases recruited, there were 32% Lenke 1, 28% Lenke 2, 8%Lenke 3, 22%Lenke 5 and 10% Lenke 6. Total thoracic levels involved were 333, whereas lumbar levels were 81. The mean total weight of bone graft obtained per case was 36.5 ± 13.7 g. The total weight of lumbar bone graft to the number of lumbar fusion levels (4.5 ± 1.2 g/fusion level) was significantly higher than the total weight of thoracic bone graft to the number of thoracic fusion levels (3.2 ± 1.2 g/fusion level). The amount of bone graft was obtained was highest from lumbar spinous process (42%), followed by thoracic spinous process (32%), lumbar lamina (29%), lumbar facet (28%), thoracic lamina (25%), thoracic facet (22%), and thoracic transverse process (21%). Conclusions: Lumbar vertebra provided more bone graft than thoracic vertebra. Spinous processes contributed the highest amount of local bone graft in the thoracic and lumbar spine.